A TYPOLOGY OF LANGUAGE LEARNING STRATEGIES USED BY EFL STUDENTS AT JUNIOR HIGH SCHOOL - Taryadi, Yudi (2007)
This study was mainly trying to find the language learning strategies (LLS) junior high school students applied in learning English. It explored the most frequent LLS used by the whole students and students categorized as good language learners. It also investigated the relationship between the LLS students applied and their achievement. In relation with the 2004 English curriculum for junior high school, this study also explored whether students' LLS were relevant to the strategic competence and attitude towards learning English the curriculum proposes. The study employed descriptive and correlative quantitative methods. There were three kinds of data collection methods, i.e. questionnaire, document analysis, and interviews. The questionnaire was used to gain an initial picture of the students' language learning strategies, the documents analysis was used to identify the students' achievement, and the interview was conducted to clarify students' answers to the questions in the questionnaire and to gain more insight into the LLS they applied in learning English.The result of this study shows that 1) some indicators of metacognitive strategy are the most frequent strategies that whole students and good learners apply in learning English, 2) there are indicators of the most frequent LLS used by good language learners that are not included in the most frequent LLS used by the overall students, 3) there is a positive correlation between students' learning strategies and students' achievement in learning English for the overall respondents, and 4) to certain extent, the 2004 English curriculum are relevant to students' learning strategies in learning English.It is hoped that the findings of this study will be useful for teachers, text book writers as well as curriculum designers. Hopefully this study will also inspire other researchers who are interested in conducting research on other aspects of language learning strategies.